Inspirasi Nderes Literasi dalam Gerakan Abadikan Kenangan dalam Tulisan - Sukaisih, Tin (Journal of Innovation in Teaching and Instructional Media, 2021)
One of the aims of the inspirational literacy movement is to provide more input or fill the reading garden to provide access to information for the public to realize lifelong learning. For example, writing a daily story on Facebook with a hashtag a paragraph a day, or a day of poetry, or 30 days of non-stop writing stories today. The research method used in this research is qualitative with a case study approach. The results of the study show that the form of literacy testing activities to perpetuate memories in writing is driven by volunteers and spearheads in carrying out various writing activities every week or month that can be recorded. This model of inspiration for literacy studies can be a driving force for advocacy activities in the field of literacy in schools and communities and other strategic partners as a driver of literacy activities that have been designed by the literacy research team. All activities that have been carried out are supported by promotional efforts through social media as the main media.